Risk Factors for Enzootic Leukosis in Dairy Cattle from the Brazilian Amazon - Barbosa da Silva, Tamyres Izarelly; Kohara Melchior, Leonardo Augusto; Santos, Priscila Souza; Reckziegel, Guilherme Henrique; Gomes, Yuri Almeida; Carvalho Fernandes, Artur Cesar; da Silva, Daniel Dias; Baptista Filho, Luiz Carlos Fontes; Honório de Melo, Lúcio Esmeraldo (Acta Scientiae Veterinariae, 2019)
Background: Enzootic bovine leukosis (EBL) is a viral and lymphoproliferative disease that attributes negative economic impacts to dairy farming. The immunosuppressive condition of these bovines favors the development of bacterial diseases such as tuberculosis, brucellosis, and bovine leptospirosis, which implications to the public health given that they are zoonosis. Diagnosis and control of EBL are neglected in cattle rearing, allowing their dissemination, especially in developing countries. In this sense, the objective of this study was to analyze the risk factors of EBL in dairy cattle from the Brazilian Amazon. Materials, Methods & Results: In order to identify the BLV-infected animals (527 serological samples), we used the agarose gel immunodiffusion serological test (IDGA) to diagnose the EBL and characterize the risk factors through the application of epidemiological questionnaires. We used the logistic regression test to evaluate the existence of a significant association between the variables. The EBL frequency in the study area was 14.42%. We detected seroreagent bovines in all municipalities evaluated with 95% of the properties showing outbreaks of the disease. The reuse of needles was the risk factor with the most significant statistical association (P < 0.01; OR = 2.16). Discussion: The origin of EBL in the Brazilian Amazon is probably related to the expansion of dairy cattle in the 1980s, which, at first, demanded the importation of cattle for the fast formation of the herds, without complying with the sanitary criteria of animal commercialization. The frequency of EBL in the Rio Branco microregion is below the estimated national average, as well as the regional level. The reduced influx of animals due to the geographical situation of Acre, since it is an area of greater physical isolation due to forest and river barriers, may influence the observed frequency. Different environmental conditions, herd size, cattle management, genetics and particularities of the diagnostic techniques should also be considered. The Rio Branco microregion can currently be considered as an area of medium frequency for BLV infection, a situation that ranges from 11 to 30% in the occurrence rate. When compared to herds with low infection frequency (<10%), the elimination of seroreagent animals and their respective outbreaks become more expensive in areas of medium or high frequency. As for the number of outbreaks detected, the finding reflects the degree of negligence regarding the prophylactic measures of EBL since it is a silent propagation disease, as well as the implications for the absence of official control and eradication programs in Brazil. According to the final logistic regression model, the reuse of needles for vaccinations, deworming, and for applying other drugs in different animals was the risk factor of greater association in the region, explaining the widespread occurrence of EBL in the studied farms. In Canadian herds, this practice also was associated with an increase in clinical cases. It is known that only 0.1 mL of blood is necessary as a minimal infectious dose of BLV. However, despite the relevance of this variable, it is little studied in epidemiological surveys, and this practice continues to be repeated in cattle. In conclusion, the wide dissemination of EBL in the dairy herds of the region is related to the practice of reusing needles and its relevance in the iatrogenic transmission of the disease